Women in limbo: the dichotomy of nationalism and modernity in the image of the bengali woman - Ahmed, Anika Mariam (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2012.